Various innovative UV spectroscopic methodologies for concurrent estimation of dapagliflozin and vildagliptin in combined tablet - Ashim Kumar Sen, Satish B. Khatariya, Dhanya B. Sen, Rajesh A. Maheshwari, Aarti S. Zanwar, Ramaswamy Velmurugan (Journal of Applied Pharmaceutical Science, 2023)
Improved glycemic regulation in people with diabetes mellitus can be achieved with a fixed-dose combination (tablets) comprising dapagliflozin 10 mg and vildagliptin 100 mg. The proposed research suggests five spectrophotometric methodologies namely simultaneous equation, absorbance ratio, second derivative zero crossing, ratio difference, and first derivative of ratio spectra methods for the simultaneous assessment of the combined tablet that are straightforward, fast, easy, accurate, and reproducible. The concentration series for DPZ showed a strong linear correlation between 0.5 and 10 μg/ml for the first, second, third, and fourth methods and between 1 and 15 μg/ml for the fifth method. However, VGT displayed exceptional linear association in the sequence of 5–100 μg/ml for the first, second, third, and fourth methods; 10–150 μg/ml for the fifth method. The outcome of precision studies was evaluated in terms of % RSD, following International Conference on Harmonization guideline acceptable limits (?2), which shows good repeatability, low intra, and interday variability, indicating an excellent precision of the developed methods. The outcome of recovery studies ranged from 96% to 103% for both the drug suggesting the suitability of the proposed methods. Percentage recovery indicates that there was no interference from tablet excipients. Moreover, the low limit of detection and the limit of quantification values prove the sensitivity of the proposed methods. The projected methods were successfully applied for the quantitative determination of both drugs. Sample solutions were analyzed six times and experimental values were found to be within 98% and 101% for both the drugs. Proposed methods were compared with reported methods in terms of their name of methods, range, sensitivity, specificity, solvents used, and application. The proposed methods are found to be comparable with the reported methods and can cover up shortcomings and thus can be utilized as alternative methods for the simultaneous assessment of dapagliflozin and vildagliptin in the combined formulation.
Keywords: Dapagliflozin, vildagliptin, diabetes mellitus, UV spectroscopic methods, tablet formulati